pyobs - An Observatory Control System for Robotic Telescopes - Husser, Tim-Oliver; Hessman, Frederic V.; Martens, Sven; Masur, Tilman; Royen, Karl; Schäfer, Sebastian (Frontiers in Astronomy and Space Sciences, 2022)
We present a Python-based framework for the complete operation of a robotic telescope observatory. It provides out-of-the-box support for many popular camera types while other hardware like telescopes, domes, and weather stations can easily be added via a thin abstraction layer to existing code. Common functionality like focusing, acquisition, auto-guiding, sky-flat, acquisition, and pipeline calibration are ready for use. A remote-control interface, a “mastermind”for truly robotic operations as well as an interface to the Las Cumbres Observatory observation portal is included. The whole system is fully configurable and easily extendable. We are currently running pyobs successfully on three different types of telescopes, of which one is a siderostat for observing the Sun. pyobs uses open standards and open software wherever possible and is itself freely available.